2006
DOI: 10.1002/ffj.1766
|View full text |Cite
|
Sign up to set email alerts
|

Volatile composition and olfactory profile of pennyroyal (Mentha pulegium L.) plants

Abstract: The composition of volatile oil extracts of pennyroyal (Mentha pulegium L.) plants was investigated by gas chromatography-mass spectrometry. Those volatiles responsible for the characteristic minty and pungent aroma of this plant were determined by gas chromatography-olfactometry. Volatile oil extracts were found to be rich in oxygenated monoterpenes, mainly pulegone and piperitone oxide, followed by isopulegol, piperitone and piperitenone. Major monoterpenes hydrocarbons were limonene and α α α α α-pinene, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Also, non-toasted oak woods presented characteristic floral and fruity notes, mainly due to linalool oxide, phenylethanol, ethyl phenylacetate, trans-cinnamaldehyde, β-damascenone and some unidentified compounds at retention indices 971 and 983. As far as the authors are aware, β-damascenone, a C13-norisoprenoid with fruity character identified in other natural products such as pennyroyal, 17 must and wine, and trans-cinnamaldehyde, described as spicy and cinnamon-like, have not previously been reported in oak wood extracts.…”
Section: Resultsmentioning
confidence: 93%
“…Also, non-toasted oak woods presented characteristic floral and fruity notes, mainly due to linalool oxide, phenylethanol, ethyl phenylacetate, trans-cinnamaldehyde, β-damascenone and some unidentified compounds at retention indices 971 and 983. As far as the authors are aware, β-damascenone, a C13-norisoprenoid with fruity character identified in other natural products such as pennyroyal, 17 must and wine, and trans-cinnamaldehyde, described as spicy and cinnamon-like, have not previously been reported in oak wood extracts.…”
Section: Resultsmentioning
confidence: 93%
“…Plants of this family include about 160 genera and over 3000 species grown almost all over the world especially in the Mediterranean region (Jafarpour et al, 2013). This species is known as a medicinal plant for its pharmacological and biological properties, it is used in the treatment of colds, sinusitis, cholera, food poisoning, bronchitis and tuberculosis (Shirazi et al, 2004;Díaz-Maroto et al, 2007). Several studies have examined the antimicrobial activity of this aromatic plant (Mahboubi and Haghi, 2008;Kanakis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…8 More and more compounds containing this olfactophore have been reported to occur in nature [9][10][11][12] and many have been approved as safe flavour ingredients by the Flavour and Extract Manufacturers' Association (FEMA). 13 The homologues of 3-methylthioalkanals, which contain a 1,3-oxygen-sulfur functionality occur widely as volatile aroma components of various plants, [14][15][16][17] fruit, 18 vegetables, 19 and cooked beef liver 20 and seafoods. 21 3-Methylthiodecanal is a relatively new flavour compound, which was added to the GRAS (Generally Recognized as Safe) list in 2013.…”
mentioning
confidence: 99%